Transformation by v-myb correlates with trans-activation of gene expression. - Lane, T (1990)
The v-myb oncogene of avian myeloblastosis virus causes acute myelomonocytic leukemia in chickens and transforms avian myeloid cells in vitro. Its protein product p48v-myb is a nuclear, sequence-specific, DNA-binding protein which activates gene expression in transient DNA transfection studies. To investigate the relationship between transformation and trans-activation by v-myb, we constructed 15 in-frame linker insertion mutants. The 12 mutants which transformed myeloid cells also trans-activated gene expression, whereas the 3 mutants which did not transform also did not trans-activate. This implies that trans-activation is required for transformation by v-myb. One of the transformation-defective mutants localized to the cell nucleus but failed to bind DNA. The other two transformation-defective mutants localized to the cell nucleus and bound DNA but nevertheless failed to trans-activate. These latter mutants define two distinct domains of p48v-myb which control trans-activation by DNA-bound protein, one within the amino-terminal DNA-binding domain itself and one in a carboxyl-terminal domain which is not required for DNA binding.